Ensino da matemática e aprendizagem da pessoa autista: contribuições da Teoria Instrucional de Robert Gagné - Borges, Tatiane Daby de Fatima Faria (2020)
This research pulls out from the following question: What are the theoretical and practical necessary knowledge for the teachers to teach math to autistic children on the elementary school using the Robert Gagné’s Instruction Theory perspective? Grounded on a guiding question, we intended to identify, describe and analyze the necessary theoretical and practical knowledge for the teacher to teach math to autistic students following the Instruction Theory perspective. To answer the proposed problem and the defined goals, the investigation developed by a bibliographic research. Through an analyses about the Autism Spectrum Disorder and the math taught in elementary school, the presented research portrayed the learning theories and in a very specific way, the Robert Gagné’s Instruction Theory as a theoretical reference to the effectuation of significant and efficient pedagogical practices in the maths teaching process to autistic students. We also presented an investigation about autism, the math teaching process to autistic people, the main learning theories, the importance of the teacher-researcher to the math teaching process to autistics, the instruction theory in the math’s teaching. Looking to establish an inter-relation between those knowlegdes to the proper characteristics of Autism Spectrum Disorder.